The Conservatism, Accounting, and Information Asymmetry - Kartika, Ita Yuni; Subroto, Bambang; Saraswati, Erwin; Rusydi, M.Khoiru (The International Journal of Accounting and Business Society, 2025)
Purpose — This study investigates the impact of accounting conservatism on information asymmetry in non-financial companies, aiming to validate the reputation theory.  Design/methodology/approach— This paper employs a quantitative approach using Stata 14 to analyze 2,791 observations from non-financial companies. The research focuses on Indonesia, a country characterized by concentrated ownership, which historically has led to low information asymmetry. However, the case of certain state-owned enterprises that have suffered financial losses raises concerns about the role of accounting conservatism in reducing information asymmetry and enhancing company reputation, ultimately benefiting minority shareholders. Findings — The study finds that accounting conservatism significantly reduces information asymmetry. Practical implications— Accounting conservatism can serve as an effective mechanism to reduce information asymmetry and strengthen the company's reputation, thereby improving trust among minority shareholders. Originality/value — This research contributes to understanding information asymmetry among non-financial companies listed on the Indonesian Stock Exchange. The study suggests that adopting accounting conservatism can help attract minority investors by addressing information asymmetry in concentrated ownership structures. Paper type — Research paper